Effect of Egg White Protein Supplementation Prior to Acute Resistance Training on Muscle Damage Indices in Untrained Japanese Men - Yuko Hasegawa; Yuko Mekata; Ayaka Sunami; Yuri Yokoyama; Takahiro Yoshizak; Maya Hagiwara; Kae Yanagisawa; Mika Usuda; Yasunobu Masuda; Yukari Kawano (Montenegrin Sports Academy, 2014)
The purpose of this study was to assess the effects of egg white (E) protein supplementation on the muscle damage indices and muscular soreness after acute resistance training (RT) compared with soy (S) or no protein supplementation (C). In this cross-over study, six healthy untrained men completed three RT trials. Participants were asked to consume a meat-free diet and refrain from high-intensity activities during all trial periods. On the day of RT, participants ingested one of three test beverages containing water only or water containing either 20 g of E or S protein 1.5 hours after breakfast, then performed 60 minutes of RT. Blood was drawn at baseline, before, immediately after, and 30 minutes after RT to assess blood glucose, lactate, insulin, growth hormone (GH), creatine kinase activity (CK) and cortisol levels. Urinary 3-methylhistidine (3-MetHis), urea nitrogen (UN), and creatinine (CRE) were measured using 24-h urine samples, and muscular soreness was measured by a visual analog scale. The daily protein intake was approximately 0.8 g/kg body weight in all three groups. Each lactate, GH, CK, cortisol, 3-MetHis, or muscular soreness increased significantly after RT, with no significant differences between the three groups. The UN was significantly higher in the E and S groups compared to the C group. The RT exercise protocol successfully induced blood biochemical changes, muscle damage or muscle soreness in all three groups with no significant differences, and pre-exercise protein supplementation taken in excess may accelerate protein catabolism.